Codifying conceptual information in descriptive terminology management - Faber, Pamela; Tercedor Sánchez, Maribel (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractMartín Mingorance's Functional-Lexematic Model (FLM) and Mel'cuk's Meaning Text Theory (MTT) are two complementary models of lexical description, which can also be applied to the description of terminological information. The FLM is compatible with general terminology theory because it envisions a lexicon structured onomasiologically in terms of areas of meaning or lexical domains. The MTT is also applicable because its lexical functions can be used to represent both paradigmatic and syntagmatic information within specialized texts. The combination of these two models permits the formalization of different translation-oriented types of terminological information, and is an aid to non-specialists who need to structure a specialized field.